A multi-component alloy / carbon black composite absorbing material and preparation method thereof

By combining multi-component alloy with carbon black, using vacuum air atomization powdering and ball milling mixing technology, multi-component alloy/carbon black composite absorbing materials are prepared, which solves the narrow bandwidth and high preparation cost of existing absorbing materials. The problem of this method achieves the effects of strong reflection loss, wide absorption frequency band and low density.

CN119255592BActive Publication Date: 2025-02-25XIAN RARE METAL MATERIALS RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411796114.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The effective absorption frequency width of existing high-entropy alloy/carbon black composite absorbing materials is narrow, the reflection loss is not low, and the preparation process is high and the efficiency is low, making it difficult to batch prepare.

Method used

By combining multi-component alloys mainly with magnetic loss with carbon black mainly with conductive loss, and using vacuum air atomization powder making and ball milling mixing and other processes, a multi-component alloy/carbon black composite wave absorbing material is prepared. , improve the impedance matching and absorbing performance of the material.

Benefits of technology

The characteristics of strong reflection loss, wide absorption frequency band and low density are achieved, which solves the problems of low reflection loss of materials and narrow absorption frequency bands, and reduces the preparation cost and improves production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255592B_ABST
    Figure CN119255592B_ABST
Patent Text Reader

Abstract

The present invention discloses a multi-component alloy / carbon black composite wave absorbing material. The molecular formula of the composite wave absorbing material is (Fe 50 Co 20 Si a Al b Ni c )‑xC; The present invention also discloses a method for preparing a composite absorbing material, which comprises the following steps: step 1, preparation of multi-component alloy spherical powder; step 2, ball milling and mixing powder; step 3, spray granulation; step 4, first flaking; step 5, dry grinding; step 6, second flaking. The present invention obtains a composite absorbing material by compounding a multi-component alloy with mainly magnetic loss and a carbon material with mainly conductive loss. The composite absorbing material can overcome the problems of low reflection loss and narrow absorption band when the multi-component alloy is used alone, and narrow effective absorption band and poor oxidation resistance when carbon black is used alone. The combination of the two can improve the impedance matching of the material, which is suitable for the technical field of electromagnetic shielding absorbing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic shielding and absorbing materials, and in particular relates to a multi-component alloy / carbon black composite absorbing material and a preparation method thereof. Background Art

[0002] There are more and more applications of absorbing materials in military and civilian fields, and their application requires that the absorbing materials meet the requirements of "thin, light, wide and strong".

[0003] In view of the above background, it is urgent to develop high-demand absorbing materials to meet the current and future great demand for high-performance absorbing materials in the field of electromagnetic wave absorption and stealth. High entropy alloys / multi-component alloys are composed of multiple main elements to form a simple solid solution structure. They have attracted much attention due to their good absorbing performance and excellent corrosion resistance and high-temperature oxidation resistance. However, the high entropy alloys reported so far are mainly dominated by magnetic loss, with small contributions from resistance loss and dielectric loss. Therefore, the effective absorption bandwidth (band width of reflection loss RL<-10dB) of this type of material is narrow, usually not higher than 5 GHz. In addition, due to the single loss mechanism of high entropy alloys, it is difficult to obtain the best impedance matching, so it is difficult to obtain extremely low reflection loss, and the lowest reflection loss is usually not less than -50dB.

[0004] The Chinese invention patent "A high entropy alloy / carbon black composite electromagnetic absorbing material and its preparation method" (Announcement No. CN114309586B) is obtained by high-energy ball milling of five kinds of powders, namely, metal iron powder, metal nickel powder, metal chromium powder, metal aluminum powder and carbon black for 60h~90h (FeNiCrAl a ) x C y High entropy alloy / carbon black composite electromagnetic absorbing material, although a lower reflection loss value (RL min is -50.91dB), but the effective absorption frequency band is only 2.36GHz. In addition, long-term high-energy ball milling of single metal powders, especially aluminum powder, will pose certain safety hazards. Furthermore, the method of directly mixing four single metal powders with carbon black for high-energy ball milling to prepare high-entropy alloy / carbon black composite materials may result in multiple products, and the purity of the high-entropy alloy / carbon black composite materials is difficult to guarantee. Finally, the high-energy ball milling method of single powders is used to prepare high-entropy alloy / carbon black composite absorbing materials. The raw material cost is high, the efficiency is low, and it is difficult to prepare in batches.

[0005] Therefore, it is urgent to develop composite absorbing materials with strong reflection loss and wide absorption band. Summary of the invention

[0006] The purpose of the present invention is to overcome the deficiencies in the above-mentioned prior art and provide a multi-component alloy / carbon black composite absorbing material. The composite absorbing material is obtained by compounding a multi-component alloy with mainly magnetic loss and a carbon material with mainly conductive loss, which is beneficial to improving the impedance matching of the material, and ultimately increasing the maximum reflection loss of the material and broadening the effective absorbing frequency band of the material, thereby obtaining the characteristics of strong reflection loss, wide absorption frequency band and relatively low density, and solving the problem that the low reflection loss value and wide effective absorption frequency band of the composite absorbing material cannot be taken into account at the same time.

[0007] To achieve the above object, the technical solution adopted by the present invention is: a multi-component alloy / carbon black composite absorbing material, characterized in that the molecular formula of the composite absorbing material is (Fe 50 Co 20 Si a Al b Ni c )-xC, the value range of a is 13~21, the value range of b is 8~11, the value range of c is 1~6, the sum of a, b and c is 30, and x is the mass percentage of C element, and x is 0.5%~5%.

[0008] In addition, the present invention also discloses a method for preparing the above-mentioned multi-component alloy / carbon black composite absorbing material, which is characterized in that the preparation method comprises the following steps:

[0009] Step 1: Preparation of multi-component alloy spherical powder: Fe, Co, Si, Al, and Ni are weighed, and vacuum suspension smelting is performed to obtain an ingot, and after removing the surface oxide scale, the ingot is placed in a vacuum gas atomization device for gas atomization powder making to obtain a multi-component alloy spherical powder;

[0010] Step 2: ball milling mixed powder: the multi-component alloy spherical powder obtained in step 1 and carbon black are placed in a ball mill, anhydrous ethanol and stainless steel grinding balls are added for ball milling to obtain a mixed slurry;

[0011] Step 3, spray granulation: putting the mixed slurry obtained in step 2 into a spray dryer for spray granulation to obtain a spherical first powder;

[0012] Step 4, first flaking: putting the spherical first powder obtained in step 3 into a ball mill, adding anhydrous ethanol and zirconium dioxide grinding balls for ball milling, and drying to obtain a flaky second powder;

[0013] Step 5, dry grinding: putting the flaky second powder obtained in step 4 into a ball mill, adding zirconium dioxide grinding balls for dry grinding to obtain a third powder;

[0014] Step 6: Second flaking: put the third powder obtained in step 5 into a ball mill, add anhydrous ethanol and zirconium dioxide grinding balls for ball milling, and obtain multi-component alloy / carbon black composite absorbing material powder after drying.

[0015] The present invention firstly obtains a spherical or quasi-spherical multi-component alloy spherical powder with a high alloying degree and stable performance by vacuum gas atomization powder preparation. The alloying degree of the multi-component alloy spherical powder is much higher than that of a high entropy alloy / multi-component alloy powder obtained by high-energy ball milling of a metal single substance powder, and the preparation process is simpler, the efficiency is high, and mass production is possible; then the multi-component alloy spherical powder is ball-milled and mixed with carbon black to obtain a uniformly mixed slurry, spherical composite powder is prepared by spray granulation, and then two flaking processes are performed to obtain a multi-component alloy / carbon black composite absorbing material powder with excellent performance;

[0016] The first flaking treatment can obtain a larger flaky powder, but as the ball milling is carried out for a long time, the flaked particles will gradually break, the width and width-to-thickness ratio will decrease, and the thickness will be difficult to continue to decrease; this is because the particles of the composite powder are constantly getting smaller, and the grinding balls of larger sizes (diameter 5mm and above) are difficult to act on small particles. Therefore, the present invention adopts a two-time ball milling method to obtain a thin flaky composite powder: first, the second powder after the first flaking is dry-milled for a short time to quickly break it to obtain fine particles, and then it is subjected to a second flaking treatment to increase the powder width and reduce the thickness of the lamellae to obtain a thin flaky multi-component alloy / carbon black composite absorbing material.

[0017] The present invention uses zirconium dioxide grinding balls in steps 4 to 6 because the multi-component alloy powder, which accounts for a relatively large proportion of the powder, has a body-centered cubic structure with high hardness and strength, and flaking it requires zirconium dioxide grinding balls with higher hardness.

[0018] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the mass purity of Fe, Co, Si, Ni, and Al in step one is not less than 99%.

[0019] The method for preparing the above-mentioned multi-component alloy / carbon black composite absorbing material is characterized in that the vacuum suspension melting system in step 1 is: overturning melting 3 times, the melting temperature is 1500°C~1600°C, and the insulation time is 5min~30min.

[0020] The present invention ensures uniform alloy composition by controlling the temperature, holding time and number of flipping melting times of vacuum suspension melting, which is beneficial to subsequent acquisition of multi-component alloy spherical powder with uniform composition.

[0021] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the particle size of the carbon black in step 2 is 200nm~500nm, the mass of the carbon black is 0.5%~5.0% of the total mass of the multi-component alloy spherical powder and the carbon black, and the mass purity of the carbon black is not less than 99.9%.

[0022] The present invention adopts carbon black with a particle size of 200nm-500nm so as to make the carbon black evenly coated on the surface of multi-component alloy spherical powder with a larger size.

[0023] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the sizes of the stainless steel grinding balls in step 2 include Ф10mm, Ф8mm and Ф3mm, the mass ratio of the Ф10mm, Ф8mm and Ф3mm stainless steel grinding balls is 3:1:6, and the ball milling system is: rotation speed 400r / min~500r / min, ball milling time 12h~24h, and pause for 5min every 30min of ball milling.

[0024] The invention controls the size and proportion of stainless steel grinding balls and limits the rotation speed and time of ball milling to strongly impact, grind and stir multi-component alloy spherical powder and carbon black, so as to reduce the particle size of the multi-component alloy spherical powder and improve the uniformity of the mixing of the two.

[0025] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the temperature of the spray granulation in step three is 120° C. to 150° C., and the particle size of the first powder is 15 μm to 30 μm.

[0026] The present invention can obtain the first powder with high surface activity and uniform particles by limiting the temperature of spray granulation.

[0027] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the sizes of the zirconium dioxide grinding balls in step 4 include Ф10mm and Ф5mm, the mass ratio of the Ф10mm and Ф5mm zirconium dioxide grinding balls is 1:4, and the ball milling system is: rotation speed 350r / min~450r / min, ball milling time 12h~24h, and pause for 5min every 30min of ball milling.

[0028] The invention limits the size and mass ratio of the zirconium dioxide grinding balls because the Ø10 mm zirconium dioxide grinding balls are relatively large and heavy. If the content is too high, the powder will appear in fragments during the powder rolling process; while the Ø5 mm zirconium dioxide grinding balls are of moderate size and have moderate energy, and have a stronger collision impact on the particles, so it is easier to deform the powder and form a complete sheet; by controlling the rotation speed and time of the ball milling, in the ball milling process at a rotation speed of 350 r / min to 450 r / min, as the ball milling time is extended, the spherical particles gradually become flaky, the surface area increases, and the space charge polarization is enhanced, so that the dielectric constant of the multi-component alloy / carbon black composite absorbing material powder is improved.

[0029] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the sizes of the zirconium dioxide grinding balls in step five include Ф10mm and Ф5mm, the mass ratio of the Ф10mm and Ф5mm zirconium dioxide grinding balls is 1:4, and the ball milling system is: rotation speed 300r / min~400r / min, dry grinding time 1h~2h.

[0030] The present invention adopts a dry grinding process to quickly break the flake structure of the second powder.

[0031] The above-mentioned method for preparing a multi-component alloy / carbon black composite absorbing material is characterized in that the sizes of the zirconium dioxide grinding balls in step six include Ф3mm and Ф1.5mm, the mass ratio of the Ф3mm and Ф1.5mm zirconium dioxide grinding balls is 1:4, and the ball milling system is: rotation speed 400r / min~500r / min, ball milling time 12h~24h, and pause for 5min every 30min of ball milling.

[0032] The present invention can flaky and further thin the third powder by using zirconium dioxide grinding balls with smaller diameters and limiting the mass ratio of the grinding balls. This is because the smaller the diameter of the grinding balls, the smaller the gaps between the grinding balls, making it easier to act on smaller particles, thereby facilitating the acquisition of thinner flaky powders.

[0033] Compared with the prior art, the present invention has the following advantages:

[0034] 1. The present invention obtains a multi-component alloy / carbon black composite absorbing material by compounding a multi-component alloy with mainly magnetic loss and a carbon material with mainly conductive loss. This can not only overcome the problems of low reflection loss and narrow absorption band when the multi-component alloy is used alone, but also overcome the problems of poor oxidation resistance and narrow effective absorption band when used alone as a absorbing agent. The combination of the two is conducive to improving the impedance matching of the material, ultimately increasing the maximum reflection loss of the material and broadening the effective absorption band of the material, and can obtain a multi-component alloy / carbon black composite absorbing material with strong reflection loss, wide absorption band and relatively low density, and a low-cost composite absorbing material that can be prepared in large quantities.

[0035] 2. The present invention adopts the method of vacuum gas atomization alloy ingot casting to batch prepare multi-component alloy spherical powder with a high degree of alloying, reduce costs and improve production efficiency; by compounding the multi-component alloy with electromagnetic loss as the main component and the carbon material with resistance loss as the main component, the impedance matching of the absorbing material is improved through the synergistic effect of the two loss mechanisms, and finally the reflection loss of the material is improved and the effective absorbing frequency band is broadened; then, by adopting the preparation process of ball milling mixing + spray granulation + secondary flaking treatment, it is conducive to obtaining a flaked composite absorbing material with uniform mixing and thin thickness. In addition, the anisotropy of the microstructure of the multi-component alloy / carbon black composite absorbing material of the present invention can break through the snoke limit and achieve a higher magnetic permeability, thereby improving the absorbing performance of the material.

[0036] 3. The multi-component alloy / carbon black composite absorbing material prepared by the present invention comprises a multi-component alloy and uniformly distributed carbon black. The composite absorbing material has excellent comprehensive performance, with a maximum reflection loss of -53.0 dB, and the widest effective absorbing frequency band (frequency band range of RL<-10 dB) when the thickness is 1.6 mm, reaching 8.6 GHz.

[0037] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is a microstructure morphology diagram of the multi-component alloy spherical powder in Example 1 of the present invention.

[0039] Figure 2 This is the X-ray diffraction pattern of the multi-component alloy spherical powder in Example 1 of the present invention.

[0040] Figure 3 This is the microscopic morphology of the multi-component alloy spherical powder and carbon black after mixed ball milling in Example 1 of the present invention.

[0041] Figure 4 This is a microstructure morphology diagram of the flaky second powder in Example 1 of the present invention.

[0042] Figure 5 This is a reflection loss-frequency diagram of the multi-component alloy / carbon black composite absorbing material powder prepared in Example 1 of the present invention.

[0043] Figure 6 This is a reflection loss-frequency diagram of the multi-component alloy absorbing material prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0044] Example 1

[0045] The molecular formula of the composite absorbing material of this embodiment is (Fe50 Co 20 Si 13 Al 11 Ni6)- 0.5%C.

[0046] The preparation method of this embodiment comprises the following steps:

[0047] Step 1: Preparation of multi-component alloy spherical powder: According to the corresponding components, five raw materials of Fe, Co, Si, Al and Ni with a purity of 99.0% are weighed, and vacuum suspension smelting is performed to obtain an ingot. After removing the surface oxide skin, the ingot is placed in a vacuum gas atomization equipment for gas atomization powder making to obtain Fe 50 Co 20 Si 13 Al 11 Ni6 multi-component alloy spherical powder; the vacuum suspension melting system is: overturning melting 3 times, the melting temperature is 1500°C, and the heat preservation is 30 minutes;

[0048] Step 2: Ball milling: The Fe 50 Co 20 Si 13 Al 11 Ni6 multi-component alloy spherical powder and carbon black with a purity of 99.9% are placed in a ball mill, anhydrous ethanol and stainless steel grinding balls of 10 mm, 8 mm and 3 mm are added, and the ball milling is performed at a speed of 400 r / min for 24 hours, and a 5-minute pause is performed every 30 minutes of ball milling to obtain a mixed slurry; the particle size of the carbon black is 200 nm to 350 nm, and the mass of the carbon black is the Fe 50 Co 20 Si 13 Al 11 0.5% of the total mass of Ni6 multi-component alloy spherical powder and carbon black; the mass ratio of the Ф10mm, Ф8mm and Ф3mm stainless steel grinding balls is 3:1:6;

[0049] Step 3, spray granulation: the mixed slurry obtained in step 2 is placed in a spray dryer for spray granulation at a temperature of 120° C. to obtain a spherical first powder with a particle size of 20 μm to 30 μm;

[0050] Step 4, first flaking: put the spherical first powder obtained in step 3 into a ball mill, add anhydrous ethanol and 10 mm and 5 mm zirconium dioxide grinding balls, and perform ball milling at a speed of 350 r / min for 24 hours, pause for 5 minutes after every 30 minutes of ball milling, and obtain a flaky second powder after drying; the mass ratio of the 10 mm and 5 mm zirconium dioxide grinding balls is 1:4;

[0051] Step 5, dry grinding: the flaky second powder obtained in step 4 is placed in a ball mill, and zirconium dioxide grinding balls with diameters of 10 mm and 5 mm are added for dry grinding at a speed of 300 r / min for 2 h to obtain a third powder;

[0052] Step 6, second flaking: put the third powder obtained in step 5 into a ball mill, add anhydrous ethanol and Ø3mm and Ø1.5mm zirconium dioxide grinding balls for ball milling at a speed of 400r / min for 24h, pause for 5min after every 30min of ball milling, and obtain a flaky multi-component alloy / carbon black composite absorbing material powder after drying.

[0053] The Fe obtained in step 1 of this embodiment 50 Co 20 Si 13 Al 11 Microstructure analysis of Ni6 multi-component alloy spherical powder, such as Figure 1 As shown, the multi-component alloy spherical powder is spherical or quasi-spherical, with a particle size range of 0 μm to 15 μm; XRD analysis results are as follows Figure 2 As shown, the phase structure of the multi-component alloy spherical powder is a single body-centered cubic (BCC) structure.

[0054] The microscopic morphology of the multi-component alloy spherical powder and carbon black after ball milling in step 2 of this embodiment is analyzed. Figure 3 As shown, after ball milling, the particles are spherical or ellipsoidal, and the particle size ranges from 1μm to 15μm.

[0055] The microstructure of the flaky second powder prepared in this embodiment is analyzed. Figure 4 As shown in the figure, the powder is flaky, with a relatively smooth surface, a thickness of 1μm~4μm, and a flaky particle size of 2μm~20μm. The electromagnetic parameters of the multi-component alloy / carbon black composite absorbing material powder were tested using a network vector analyzer combined with a coaxial method (the mass ratio of powder to paraffin was 7:3). The results are shown in Figure 5 As shown, the minimum reflection loss value of the multi-component alloy / carbon black composite absorbing material powder reaches -53.0 dB, and the corresponding electromagnetic wave frequency is 4.8 GHz. When the thickness of the multi-component alloy / carbon black composite material is 1.6 mm, the effective absorption frequency band is the widest, reaching 8.6 GHz; indicating that the multi-component alloy / carbon black composite absorbing material powder prepared in this embodiment has excellent absorbing performance.

[0056] Comparative Example 1

[0057] The difference between this comparative example and Example 1 is that in step 2, only the Fe 50 Co 20 Si 13 Al 11The Ni6 multi-component alloy spherical powder was ball milled without adding carbon black.

[0058] The electromagnetic parameters of the multi-component alloy absorbing material prepared in this comparative example were tested using a network vector analyzer and a coaxial method (the mass ratio of powder to paraffin was 7:3). The results are as follows: Figure 6 As shown, the minimum reflection loss value of the multi-component alloy absorbing material is only -16.4dB, and the corresponding electromagnetic wave frequency is 4.7GHz. The multi-component alloy absorbing material has the widest effective absorption frequency band of 3.0GHz when the thickness is 2.9mm. Compared with the multi-component alloy / carbon black composite absorbing material powder prepared in Example 1, the reflection loss of this comparative example is larger, the effective absorption frequency is narrower, and the thickness is thicker. This shows that the addition of carbon black in Example 1 can significantly reduce the reflection loss of the composite absorbing material, increase the effective absorption bandwidth, and reduce the thickness of the composite absorbing material. The low-density carbon material also reduces the density of the material, meeting the concept and requirements of "thin, light, wide, and strong" required for the absorbing material.

[0059] Example 2

[0060] The molecular formula of the composite absorbing material of this embodiment is (Fe 50 Co 20 Si 21 Al8Ni1)- 5.0%C.

[0061] The preparation method of this embodiment comprises the following steps:

[0062] Step 1: Preparation of multi-component alloy spherical powder: According to the corresponding components, five raw materials of Fe, Co, Si, Al and Ni with a purity of 99.3% are weighed, and vacuum suspension smelting is performed to obtain an ingot. After removing the surface oxide skin, the ingot is placed in a vacuum gas atomization equipment for gas atomization powder making to obtain Fe 50 Co 20 Si 21 Al8Ni1 multi-component alloy spherical powder; the vacuum suspension melting system is: overturning melting 3 times, the melting temperature is 1600°C, and the heat preservation is 5 minutes;

[0063] Step 2: Ball milling: The Fe 50 Co 20 Si 21 Al8Ni1 multi-component alloy spherical powder and carbon black with a purity of 99.95% are placed in a ball mill, anhydrous ethanol and stainless steel grinding balls of 10 mm, 8 mm and 3 mm are added, and the ball milling is performed at a speed of 500 r / min for 12 hours, and a 5-minute pause is performed every 30 minutes of ball milling to obtain a mixed slurry; the particle size of the carbon black is 400 nm to 500 nm, and the mass of the carbon black is the Fe 50 Co 20Si 21 5.0% of the total mass of Al8Ni1 multi-component alloy spherical powder and carbon black; the mass ratio of the Ф10mm, Ф8mm and Ф3mm stainless steel grinding balls is 3:1:6;

[0064] Step 3, spray granulation: the mixed slurry obtained in step 2 is placed in a spray dryer for spray granulation at a temperature of 150° C. to obtain a spherical first powder with a particle size of 15 μm to 25 μm;

[0065] Step 4, first flaking: put the spherical first powder obtained in step 3 into a ball mill, add anhydrous ethanol and 10 mm and 5 mm zirconium dioxide grinding balls, and perform ball milling at a speed of 450 r / min for 12 hours, pause for 5 minutes after every 30 minutes of ball milling, and obtain a flaky second powder after drying; the mass ratio of the 10 mm and 5 mm zirconium dioxide grinding balls is 1:4;

[0066] Step 5, dry grinding: the flaky second powder obtained in step 4 is placed in a ball mill, and zirconium dioxide grinding balls with diameters of 10 mm and 5 mm are added for dry grinding at a speed of 400 r / min for 1 hour to obtain a third powder;

[0067] Step 6, second flaking: put the third powder obtained in step 5 into a ball mill, add anhydrous ethanol and Ø3mm and Ø1.5mm zirconium dioxide grinding balls for ball milling at a speed of 500r / min for 12h, pause for 5min after every 30min of ball milling, and obtain a flaky multi-component alloy / carbon black composite absorbing material powder after drying.

[0068] According to the test, the minimum reflection loss of the flaky multi-component alloy / carbon black composite absorbing material powder prepared in this embodiment reaches -51.6 dB, and the effective absorption frequency band is the widest when the thickness is 1.8 mm, reaching 8.7 GHz.

[0069] Example 3

[0070] The molecular formula of the composite absorbing material of this embodiment is (Fe 50 Co 20 Si 17 Al9Ni4)- 2.8%C.

[0071] The preparation method of this embodiment comprises the following steps:

[0072] Step 1: Preparation of multi-component alloy spherical powder: According to the corresponding components, five raw materials of Fe, Co, Si, Al and Ni with a purity of 99.5% are weighed, and vacuum suspension smelting is performed to obtain an ingot. After removing the surface oxide skin, the ingot is placed in a vacuum gas atomization equipment for gas atomization powder making to obtain Fe 50 Co 20 Si 17Al9Ni4 multi-component alloy spherical powder; the vacuum suspension melting system is: overturning melting 3 times, the melting temperature is 1550°C, and the heat preservation is 15 minutes;

[0073] Step 2: Ball milling: The Fe 50 Co 20 Si 17 Al9Ni4 multi-component alloy spherical powder and carbon black with a purity of 99.93% are placed in a ball mill, anhydrous ethanol and stainless steel grinding balls of 10 mm, 8 mm and 3 mm are added, and the ball milling is performed at a speed of 430 r / min for 18 hours, and a 5-minute pause is performed every 30 minutes of ball milling to obtain a mixed slurry; the particle size of the carbon black is 400 nm to 500 nm, and the mass of the carbon black is the Fe 50 Co 20 Si 17 2.8% of the total mass of Al9Ni4 multi-component alloy spherical powder and carbon black; the mass ratio of the Ф10mm, Ф8mm and Ф3mm stainless steel grinding balls is 3:1:6;

[0074] Step 3, spray granulation: placing the mixed slurry obtained in step 2 into a spray dryer for spray granulation at a temperature of 135° C. to obtain a spherical first powder with a particle size of 20 μm to 30 μm;

[0075] Step 4, first flaking: put the spherical first powder obtained in step 3 into a ball mill, add anhydrous ethanol and 10 mm and 5 mm zirconium dioxide grinding balls, and perform ball milling at a speed of 400 r / min for 20 hours, pause for 5 minutes after every 30 minutes of ball milling, and obtain a flaky second powder after drying; the mass ratio of the 10 mm and 5 mm zirconium dioxide grinding balls is 1:4;

[0076] Step 5, dry grinding: the flaky second powder obtained in step 4 is placed in a ball mill, and zirconium dioxide grinding balls with diameters of 10 mm and 5 mm are added for dry grinding at a speed of 350 r / min for 1.5 h to obtain a third powder;

[0077] Step 6, second flaking: put the third powder obtained in step 5 into a ball mill, add anhydrous ethanol and Ø3mm and Ø1.5mm zirconium dioxide grinding balls, and mill at a speed of 450r / min for 20h, pause for 5min after every 30min of ball milling, and obtain a flaky multi-component alloy / carbon black composite absorbing material powder after drying.

[0078] According to the test, the minimum reflection loss of the flaky multi-component alloy / carbon black composite absorbing material powder prepared in this embodiment reaches -50.9 dB, and the effective absorption frequency band is the widest when the thickness is 1.7 mm, reaching 8.0 GHz.

[0079] Example 4

[0080] The molecular formula of the composite absorbing material of this embodiment is (Fe 50 Co 20 Si 15 Al 10 Ni5)-3.6%C.

[0081] The preparation method of this embodiment comprises the following steps:

[0082] Step 1: Preparation of multi-component alloy spherical powder: According to the corresponding components, five raw materials of Fe, Co, Si, Al and Ni with a purity of 99.5% are weighed, and vacuum suspension smelting is performed to obtain an ingot. After removing the surface oxide skin, the ingot is placed in a vacuum gas atomization equipment for gas atomization powder making to obtain Fe 50 Co 20 Si 15 Al 10 Ni5 multi-component alloy spherical powder; the vacuum suspension melting system is: overturning melting 3 times, the melting temperature is 1580°C, and the heat preservation is 10 minutes;

[0083] Step 2: Ball milling: The Fe 50 Co 20 Si 15 Al 10 Ni5 multi-component alloy spherical powder and carbon black with a purity of 99.95% are placed in a ball mill, anhydrous ethanol and stainless steel grinding balls of 10 mm, 8 mm and 3 mm are added, and the ball milling is performed at a speed of 480 r / min for 16 hours, and a 5-minute pause is performed every 30 minutes of ball milling to obtain a mixed slurry; the particle size of the carbon black is 250 nm to 400 nm, and the mass of the carbon black is the Fe 50 Co 20 Si 15 Al 10 3.6% of the total mass of Ni5 multi-component alloy spherical powder and carbon black; the mass ratio of the Ф10mm, Ф8mm and Ф3mm stainless steel grinding balls is 3:1:6;

[0084] Step 3, spray granulation: placing the mixed slurry obtained in step 2 into a spray dryer for spray granulation at a temperature of 140° C. to obtain a spherical first powder with a particle size of 15 μm to 25 μm;

[0085] Step 4, first flaking: put the spherical first powder obtained in step 3 into a ball mill, add anhydrous ethanol and 10 mm and 5 mm zirconium dioxide grinding balls, and perform ball milling at a speed of 420 r / min for 20 hours, pause for 5 minutes after every 30 minutes of ball milling, and obtain a flaky second powder after drying; the mass ratio of the 10 mm and 5 mm zirconium dioxide grinding balls is 1:4;

[0086] Step 5, dry grinding: the flaky second powder obtained in step 4 is placed in a ball mill, and zirconium dioxide grinding balls with diameters of 10 mm and 5 mm are added for dry grinding at a speed of 360 r / min for 2 h to obtain a third powder;

[0087] Step 6, second flaking: put the third powder obtained in step 5 into a ball mill, add anhydrous ethanol and Ø3mm and Ø1.5mm zirconium dioxide grinding balls, and mill at a speed of 480r / min for 16h, pause for 5min after every 30min of ball milling, and obtain a flaky multi-component alloy / carbon black composite absorbing material powder after drying.

[0088] According to the test, the minimum reflection loss of the flaky multi-component alloy / carbon black composite absorbing material powder prepared in this embodiment reaches -52.7 dB, and the effective absorption segment is the widest when the thickness is 1.9 mm, reaching 8.3 GHz.

[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent structural transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A multi-component alloy / carbon black composite absorbing material, characterized in that: The molecular formula of the composite absorbing material is (Fe 50 Co 20 Si a Al b Ni c )- xC, the value range of a is 13-21, the value range of b is 8-11, the value range of c is 1-6, the sum of a, b and c is 30, x is the mass percentage of C element, and x is 0.5%-5%; the composite absorbing material is prepared by the following method: Step 1: Preparation of multi-component alloy spherical powder: Fe, Co, Si, Al, and Ni are weighed, and vacuum suspension smelting is performed to obtain an ingot, and after removing the surface oxide scale, the ingot is placed in a vacuum gas atomization device for gas atomization powder making to obtain a multi-component alloy spherical powder; Step 2: ball milling mixed powder: the multi-component alloy spherical powder obtained in step 1 and carbon black are placed in a ball mill, anhydrous ethanol and stainless steel grinding balls are added for ball milling to obtain a mixed slurry; Step 3, spray granulation: putting the mixed slurry obtained in step 2 into a spray dryer for spray granulation to obtain a spherical first powder; Step 4, first flaking: putting the spherical first powder obtained in step 3 into a ball mill, adding anhydrous ethanol and zirconium dioxide grinding balls for ball milling, and drying to obtain a flaky second powder; Step 5, dry grinding: putting the flaky second powder obtained in step 4 into a ball mill, adding zirconium dioxide grinding balls for dry grinding to obtain a third powder; Step 6: Second flaking: put the third powder obtained in step 5 into a ball mill, add anhydrous ethanol and zirconium dioxide grinding balls for ball milling, and obtain multi-component alloy / carbon black composite absorbing material powder after drying.

2. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The mass purity of Fe, Co, Si, Ni and Al described in step 1 is not less than 99%.

3. The multi-component alloy / carbon black composite absorbing material according to claim 2, characterized in that: The vacuum suspension melting system in step 1 is: inversion melting 3 times, the melting temperature is 1500°C~1600°C, and the heat preservation is 5min~30min.

4. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The particle size of the carbon black in step 2 is 200nm~500nm, the mass of the carbon black is 0.5%~5.0% of the total mass of the multi-component alloy spherical powder and the carbon black, and the mass purity of the carbon black is not less than 99.9%.

5. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The sizes of the stainless steel grinding balls in step 2 include Ф10mm, Ф8mm and Ф3mm, the mass ratio of the Ф10mm, Ф8mm and Ф3mm stainless steel grinding balls is 3:1:6, and the ball milling system is: rotation speed 400r / min~500r / min, ball milling time 12h~24h, and pause for 5min every 30min of ball milling.

6. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The temperature of the spray granulation in step 3 is 120° C. to 150° C., and the particle size of the first powder is 15 μm to 30 μm.

7. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The sizes of the zirconium dioxide grinding balls in step 4 include Ф10mm and Ф5mm, the mass ratio of the Ф10mm and Ф5mm zirconium dioxide grinding balls is 1:4, and the ball milling system is: rotation speed 350r / min~450r / min, ball milling time 12h~24h, and pause for 5min every 30min of ball milling.

8. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The sizes of the zirconium dioxide grinding balls in step five include Ф10mm and Ф5mm, the mass ratio of the Ф10mm and Ф5mm zirconium dioxide grinding balls is 1:4, and the ball milling system is: rotation speed 300r / min~400r / min, dry grinding time 1h~2h.

9. The multi-component alloy / carbon black composite absorbing material according to claim 1, characterized in that: The sizes of the zirconium dioxide grinding balls in step six include Ф3mm and Ф1.5mm, the mass ratio of the Ф3mm and Ф1.5mm zirconium dioxide grinding balls is 1:4, and the ball milling system is: rotation speed 400r / min~500r / min, ball milling time 12h~24h, and pause for 5min every 30min of ball milling.

Citation Information

Patent Citations

  • A high entropy alloy / carbon black composite electromagnetic absorbing material and preparation method thereof

    CN114309586B

  • High-performance composite binding phase hard alloy and preparation method thereof

    CN118326222A

  • Negative electrode material for nonaqueous electrolyte battery, negative electrode, nonaqueous electrolyte battery, and manufacturing method of negative electrode material

    JP2004006206A